2014
DOI: 10.1093/nar/gku1233
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic regulation of translational reading-frame switch by ligand-responsive RNAs in mammalian cells

Abstract: Distinct translational initiation mechanisms between prokaryotes and eukaryotes limit the exploitation of prokaryotic riboswitch repertoire for regulatory RNA circuit construction in mammalian application. Here, we explored programmed ribosomal frameshifting (PRF) as the regulatory gene expression platform for engineered ligand-responsive RNA devices in higher eukaryotes. Regulation was enabled by designed ligand-dependent conformational rearrangements of the two cis-acting RNA motifs of opposite activity in -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…We have demonstrated that the formation of an upstream attenuator hairpin can be controlled by alternate base-pairing schemes to achieve −1 PRF activity regulation ( 31 ). Aiming for sequence-specific regulation of −1 PRF, we designed DNA oligonucleotides complementary to the 5′-half (6BPGC-5′-DNA) or the 3′-half (6BPGC-3′-DNA) sequences of the stem of a potent −1 PRF attenuator hairpin (6BPGC) ( 29 ) (Supplementary Figure S1A) to interfere with attenuation hairpin refolding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that the formation of an upstream attenuator hairpin can be controlled by alternate base-pairing schemes to achieve −1 PRF activity regulation ( 31 ). Aiming for sequence-specific regulation of −1 PRF, we designed DNA oligonucleotides complementary to the 5′-half (6BPGC-5′-DNA) or the 3′-half (6BPGC-3′-DNA) sequences of the stem of a potent −1 PRF attenuator hairpin (6BPGC) ( 29 ) (Supplementary Figure S1A) to interfere with attenuation hairpin refolding.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a variant of p2luc was engineered to facilitate radioactivity based −1 PRF activity analysis in vitro . The variant contains a premature −1 frame stop codon 33 nt downstream of the BamHI site of p2luc, and will be translated into a shortened −1 frame product in reticulocyte lysate ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…In support of this, hybridization of antisense linked nucleic acids (LNAs) immediately 3 0 of heptameric slippery sequences was sufficient to promote efficient -1 frameshifting in the absence of any other stimulatory element [39]. Natural attenuation of -1 PRF by stem-loop structures immediately 5 0 of coronavirus slippery sequences has also been reported [40], a phenomenon that can be replicated by hybridization of oligonucleotides complementary to sequences lying just upstream of slippery sites [41]. These studies establish the role of ncRNAs in regulating translational fidelity and suggest that regulation of -1 PRF may not be limited to miRNAs.…”
Section: Sequence-specific Regulation Of Frameshiftingmentioning
confidence: 89%
“…A canonical -1PRF element consists of a 7-nt slippery sequence X XXY YYZ (trinucleotides XXY and YYZ representing the original frame and XXX YYY representing the -1 frameshift) followed by a stable secondary structure such as a pseudoknot or a stem-loop. The Chang group first controlled -1PRF in mammalian cells (Figure 3a) by incorporating theophylline and S-adenosyl-L-homocysteine (SAH) aptamers [28]. An ON/OFF ratio of 6 was reported but the frameshifting efficiency (FE) remained low.…”
Section: Controlling Ribosomal Frameshifting By Aptamersmentioning
confidence: 99%